Metaphor in the Author’s Comments - Matevosyan, Armine (Armenian Folia Anglistika, 2006)
Metaphor is the most characteristic element of a literary text since it reflects the individual style of the author and provides the reader with some information about the secret part of his/her creativity. The article investigates the metaphors in D.H. Lawrence’s authorial comments in his stories. Authorial comments are one of the methods used in poetic speech to provide a more complete picture of the personalities of the characters involved and their speech characteristics.